Uncertain Precision and Price Reactions to Information - Subramanyam, K. R. (The Accounting Review, 1996)
[This paper models the effect of information on security prices when there is uncertainty regarding the precision of information. When uncertainty regarding precision is allowed, price response to information is neither linear nor even necessarily monotonic, because the market revises its expectation regarding the precision based on the signal realization. When the underlying information structure is conditionally multivariate normal, the price response (return) is nonlinear with the average response (response per unit of surprise) declining in the absolute magnitude of surprise. This nonlinearity occurs because the market associates lower precision with extreme news. When the precision is distributed in the form of a gamma, the returns function is unimodal in each quadrant ("S-shaped") and negatively sloped at the extremes. The extent of nonlinearity increases in the ex ante uncertainty regarding both the asset value and the precision of information.]